Śrīdatta-bhakta-rahasya : Śrīdatta, Śrīdattavibhūti, va Śrīdattabhakta yāñcẽ cāritrya va śikavaṇa - Phaḍake, Sadāśiva Krshṇa (SAMP early 20th-century Indian books project, 1931)
On the cult of Dattātreya, Hindu deity.